2018
DOI: 10.1001/jamapsychiatry.2018.1973
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Neural Basis of Psychoticlike Experiences in Adolescence During Reward Processing

Abstract: The findings are consistent with evidence implicating alterations in prefrontal and striatal function during reward processing in the etiology of psychosis. Given the nature of this nonclinical sample this may reflect a combination of aberrant salience yielding abnormal experiences and a compensatory cognitive control mechanism necessary to contextualize them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ conclusions In a previous study from the same IMAGEN sample, we provided evidence for a consistent increase in prefrontal activation during reward feedback, in the high PLEs group, between the ages of 14 and 19, which was attributed to a compensatory cognitive control mechanism 37 . The current study revealed functional alterations in parahippocampal/amygdala and insula responses during the perception of emotional faces in adolescents with high PLEs between the ages of 14 and 19 suggests a potential 'aberrant' neurodevelopmental trajectory for critical limbic areas.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…www.nature.com/scientificreports www.nature.com/scientificreports/ conclusions In a previous study from the same IMAGEN sample, we provided evidence for a consistent increase in prefrontal activation during reward feedback, in the high PLEs group, between the ages of 14 and 19, which was attributed to a compensatory cognitive control mechanism 37 . The current study revealed functional alterations in parahippocampal/amygdala and insula responses during the perception of emotional faces in adolescents with high PLEs between the ages of 14 and 19 suggests a potential 'aberrant' neurodevelopmental trajectory for critical limbic areas.…”
Section: Discussionmentioning
confidence: 51%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Aberrant activation of the amygdala during a face recognition is probably one of neuroimaging hallmarks of psychosis. In our study, we identified a large cluster centred in the right parahippocampal gyrus, including the amygdalae, hippocampal, and parahippocampal areas, which demonstrated a peak activation at a right parahippocampal region, [33][34][35][36][37][38][39][40][41][42][43][44][45][46], which demonstrated significantly lower activation for the high PLEs group at the age of 19. A study employing a similar IMAGEN sample as ours revealed that subjects with PLEs demonstrated, among other findings, increased hippocampus/amygdala activation during processing of neutral faces, compared to controls 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as age 10-11, an endorsement of psychotic like experiences items on interview is less likely to be representative of mental disorder than a similar endorsement in adolescence (26), and the persistence of psychotic-like experiences over time has been shown to be associated with a higher risk of mental disorder than isolated measurements (24; 25). Previous studies have suggested links between reward processing (and other fMRI task) activation and psychopathology in children and adolescents than the current sample (11)(27; 12). This leads to the following prediction: children who persist in endorsing psychotic-like experiences at multiple time-points over the coming years will be more prone to develop schizophrenia spectrum or depressive illnesses than other short members, and this persistence of psychopathology, and emergence of new psychopathology in follow-ups, may be associated with (or possibly predicted by) concomitant deficits in brain activation in the MID task.…”
Section: Discussionmentioning
confidence: 56%
“…Depression was measured with the K-SADS, the gold standard in this age group for diagnostic purposes; admittedly, in terms of a continuous measures of severity of depression, or of anhedonia, additional assessments might be more sensitive to individual differences in participants. Given that in middle adolescence, and in adulthood, striatal reward anticipation has been shown to be deficient in patients with schizophrenia and clinical or subthreshold depression (4)(5)(6)(11)(12), it appears that clear associations between psychopathology and brain reward anticipation signatures only emerge during adolescence. The ABCD study provides a platform through which this prediction can be tested, as the study protocol is that repeat measures of fMRI and psychopathology will be acquired in the coming years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation